The Influence of Environment, Social, Governance and Controversy on Company Value (Study on Consumer Cyclical Companies Listed on the IDX) - Rossy Perwani Putri; Robith Hudaya (International Journal of Economics, Business and Innovation Research, 2024)
One of the factors that encourages the development of go-public companies is high market capital. The consumer cyclical sector or what is often called non-primary consumer goods is an industry that produces and distributes products and services that are strongly influenced by economic conditions. This research is quantitative research. This research aims to determine the influence of the environment, social, governance and controversy on company value. The population in the research is consumer cyclical companies registered on the IDX. The sampling technique in this research uses a purposive sampling technique with characteristics appropriate to the sample used. There are certain criteria that have been set, namely; all consumer cyclical companies listed on the Indonesia Stock Exchange (BEI) in the 2020–2022 period. The results of this research have found that Social, Governance and Controversy influence Company Value. However, the environment has no influence in this research.